Yihiella yeosuensis gen. et sp. nov. (suessiaceae, dinophyceae), a novel dinoflagellate isolated from the coastal waters of Korea - Jang, Se Hyeon (Journal of phycology, 2017)
© 2016 Phycological Society of America.